THE DEVELOPMENT OF A BACHELOR’S SOFT SKILLS THROUGH PROJECT ACTIVITIES IN A FOREIGN LANGUAGE - Klets, Tatyana; Malysheva, Oksana; Presnyakova, Nadezhda; Starovoitova, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The present period of higher education modernization is characterized by the need to improve the bachelor’s professional training aimed at the comprehensive development of the student’s personality, which, along with hard skills, should have a wide range of soft skills. On the basis of the content analysis of the concept ‘soft skills’ the authors define them as universal socio-personal and general cultural skills and qualities that contribute to successful professional activities and effective interpersonal interaction. The relevance of the study is due to the fact that, despite an active discussion in the scientific literature on the development of soft skills among bachelor students, the level of these skills’ acquisition is quite low and requires a systematic and focused work to improve them.The article presents an appeal to the topic of soft skills through the practice of project activities in a foreign language. The research is aimed at the theoretical substantiation of the psychological and pedagogical effectiveness of project activities for developing soft skills and the generalization of the results of experimental training using the project method in foreign language teaching of non-linguistic students. According to the authors, project work contributes to the obtaining of a complex of non-specialized, career-important supraprofessional skills that are responsible for successful participation in the work process, high productivity and are not related to a specific subject area. Among the most relevant soft skills the authors define communicative, interpersonal and cognitive skills, emotional intelligence, management skills.